Effects of propranolol on the QT dispersion in congestive heart failure - Mesquita,Evandro Tinoco (1999)
OBJECTIVE - Studies have shown that therapy with beta-blockers reduces mortality in patients with heart failure. However, there are no studies describing the effects of propranolol on the QT dispersion in this population. The objective of this study was to assess the electrophysiological profile, mainly QT dispersion, of patients with heart failure regularly using propranolol. METHODS - Fifteen patients with heart failure and using propranolol were assessed over a period of 12 months. Twelve-lead electrocardiograms (ECG) were recorded prior to the onset of beta-blocker therapy and after 3 months of drug use. RESULTS - A significant reduction in heart rate, in QT dispersion and in QTc dispersion was observed, as was also an increase in the PR interval and in the QT interval, after the use of propranolol in an average dosage of 100 mg/day. CONCLUSION - Reduction in QT dispersion in patients with heart failure using propranolol may explain the reduction in the risk of sudden cardiac death with beta-blocker therapy, in this specific group of patients.